4(x-8)-2(x-5)+7x=

Simple and best practice solution for 4(x-8)-2(x-5)+7x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-8)-2(x-5)+7x= equation:


Simplifying
4(x + -8) + -2(x + -5) + 7x = 0

Reorder the terms:
4(-8 + x) + -2(x + -5) + 7x = 0
(-8 * 4 + x * 4) + -2(x + -5) + 7x = 0
(-32 + 4x) + -2(x + -5) + 7x = 0

Reorder the terms:
-32 + 4x + -2(-5 + x) + 7x = 0
-32 + 4x + (-5 * -2 + x * -2) + 7x = 0
-32 + 4x + (10 + -2x) + 7x = 0

Reorder the terms:
-32 + 10 + 4x + -2x + 7x = 0

Combine like terms: -32 + 10 = -22
-22 + 4x + -2x + 7x = 0

Combine like terms: 4x + -2x = 2x
-22 + 2x + 7x = 0

Combine like terms: 2x + 7x = 9x
-22 + 9x = 0

Solving
-22 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + 9x = 0 + 22

Combine like terms: -22 + 22 = 0
0 + 9x = 0 + 22
9x = 0 + 22

Combine like terms: 0 + 22 = 22
9x = 22

Divide each side by '9'.
x = 2.444444444

Simplifying
x = 2.444444444

See similar equations:

| (3v-2)(2v+1)=3v^2-11v-10 | | 4xy+3yz=-9xz-4xy | | 7.9x+1=6.9x | | 1/2x+2=(4x+1)/4 | | 18.1=p-7 | | v-9.85=6.4 | | 1/2x+2=4x+1/4 | | 27=2a+5 | | 10-x=17 | | 2xy+3yz=-5xz-2xy | | 4z-9z+2=0 | | -(8y+1)-(-7y-5)=5 | | x=-5x^2+6x+9 | | y(x)=-16x^2+64x | | a=2a+(-3) | | 500t=1000/300 | | x=-5x^2+8x+9 | | x^3+x^2+3*x+5=0 | | 2x-(5a+7x)=8x+(-3x+7a)-2a | | 3=j+2 | | f(x)=-5x^2+8x+9 | | 15(m+5)-3(8m+7)= | | 125x^2=12 | | -x^2-6x-8= | | -1=-5+I | | 6+2r-3=6r+3-3r | | 3[7x-2(y-1)]= | | 2=H-4 | | 2=H+4 | | u-1/8 | | -3x^2-6x-8= | | m^2-2*m+2=0 |

Equations solver categories